Institutions, corporate governance and corporate governance institutions: The case of Estonia - Theo J. B. M. Postma; Niels Hermes (Journal for East European Management Studies, 2003)
During the last ten years, Estonia has made strong efforts in terms of the transition to a market economy. This is particularly true with respect to the soundness and transparency of monetary and fiscal policies, the privatisation of former state-owned enterprises, the development of the financial sector and the institutional setting. This paper argues that strengthening the formal institutional setting, and in particular the corporate governance institutions, is crucial to further enhance the process of economic transition of the country. It describes the current state the corporate governance structures as compared to other countries in Central and Eastern. – – In den letzten 10 Jahren hat Estland viele Anstrengungen in der Umwandlung in eine Marktwirtschaft unternommen. Dies trifft insbesondere auf die Stabilität und Transparenz der Währungs- und Finanzpolitik zu, der Privatisierung ehemaliger Staatsbetriebe, die Entwicklung im Finanzsektor und im institutionellen Umfeld. Der Aufsatz zeigt auf, dass die Stärkung des formellen institutionellen Umfeldes und im einzelnen auch die der Bereiche der Unternehmensorganisation essentiell wichtig für den weiteren Tranformationsprozess des Landes sind. Er stellt den heutigen Stand der Unternehmensstrukturen im Vergleich zu anderen Staaten dar.
Keywords: 650; Institutions; corporate governance; Estonia; transition; Central and East European countries